Use of co‐design methodology in the development of cardiovascular disease secondary prevention interventions: A scoping review. (10th November 2022) - Talevski, Jason; Kulnik, Stefan T.; Jessup, Rebecca L.; Falls, Roman; Cvetanovska, Natali; Beauchamp, Alison
Abstract: Introduction: There is growing evidence to support the use of co‐design in developing interventions across many disciplines. This scoping review aims to examine how co‐design methodology has been used in the development of cardiovascular disease (CVD) secondary prevention interventions within health and community settings. Methods: We searched four academic databases for studies that used the co‐design approach to develop their intervention. Studies were included if consumers (adults with CVD) and key stakeholders (e.g. clinicians, service providers) were involved in the co‐design process. The review focused on methodology rather than traditional study outcomes; therefore, co‐design processes and activities were extracted and evaluated against a selected co‐design framework. Results: Twenty‐two studies were included in this review. Studies were implemented across various settings with consumers and stakeholder groups most frequently consisting of patients and healthcare professionals, respectively. Most studies specifically stated that they used a 'co‐design' approach ( n  = 10); others used terms such as participatory action research ( n  = 3), user‐centred design ( n  = 3) and community‐based participatory research ( n  = 2). Although there was variability in terminology, co‐design processes, and participants, all studies adhered to the key principles of consumer engagement. Predominant co‐design activities included semistructured interviews, focus groups, co‐design/development workshops and advisory group meetings. Intervention effectiveness was assessed in eight studies showing mixed results. Conclusions: This review provides an overview of how the co‐design approach has previously been used in the development of CVD secondary prevention interventions. These findings provide methodological considerations that can guide researchers and healthcare services when implementing co‐design to develop feasible and acceptable interventions that can improve outcomes for CVD populations. Patient or Public Contribution: No patients, service users, caregivers, people with lived experience or members of the public were involved in this scoping review. This review article was written by academics who have undertaken a significant amount of co‐design work with consumers and stakeholders.